Physical Fitness of Smoking Students Class XI State High School 9 Jambi City - Saputra, Riky; Ilham, Ilham; Yanto, Anggel Hardi (Journal of English Language and Education, 2026)
Smoking habits among school-age adolescents have the potential to cause negative health effects, particularly on physical fitness levels. This study aims to describe the physical fitness levels of smoking students in grade XI at State Senior High School 9 in Jambi City based on the results of the Indonesian Physical Fitness Test (TKJI) for ages 16–19 years. This study used a quantitative descriptive method. The study population consisted of all male students in grade XI at SMA Negeri 9 Kota Jambi in the 2025/2026 academic year, totaling 97 students. The study sample was determined using cluster random sampling, resulting in the selection of 20 male students in grade XI Phase F2 as research respondents. Data collection was conducted through smoking habit observation sheets to categorize students into active smokers, occasional smokers, and passive smokers, as well as through the Indonesian Physical Fitness Test (TKJI), which included a 60-meter run, pull-ups, a 60-second sit-up, vertical jump, and a 1200-meter run. Data analysis used quantitative descriptive analysis with percentage calculations. The results of the study show that the physical fitness level of smoking students in grade XI at State Senior High School 9 in Jambi City is generally low, with an average TKJI score of 13.7 (below average category). Based on smoking habits, active smokers had an average TKJI score of 11.25 (poor category), occasional smokers had an average score of 14.33 (moderate category), while passive smokers had an average score of 16.67 (moderate-good category). These results indicate that the more frequently students smoke, the lower their level of physical fitness.